2022
DOI: 10.1111/hex.13425
|View full text |Cite
|
Sign up to set email alerts
|

Patient, clinician and manager experience of the accelerated implementation of virtual consultations following COVID‐19: A qualitative study of preferences in a tertiary orthopaedic rehabilitation setting

Abstract: Aim To investigate the experiences of patients, clinicians and managers during the accelerated implementation of virtual consultations (VCs) due to COVID‐19. To understand how patient preferences are constructed and organized. Methods Semi‐structured interviews with patients, clinicians and managerial staff at a single specialist orthopaedic centre in the United Kingdom. The interview schedule and coding frame were based on Normalisation Process Theory. Interviews were conducted over the telephone or by video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…This may help to explain, in part, the results of a mixed methods study conducted in a UK outpatient department following the rapid implementation of a remote video consultation platform which indicated that, while all patients reported that the consultations met their needs, they were less satisfied than clinicians that they had communicated everything they wanted to (86% vs 95%) 19. A quarter of clinicians showed some recognition of this, reporting a belief that patient experience of a remote video consultation was worse than that in a face-to-face clinic 18 19. This echoes findings from primary care, where general dissatisfaction with video consultations among both patients and practitioners has been reported, emphasising a belief that the best therapeutic care is delivered in person 7.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This may help to explain, in part, the results of a mixed methods study conducted in a UK outpatient department following the rapid implementation of a remote video consultation platform which indicated that, while all patients reported that the consultations met their needs, they were less satisfied than clinicians that they had communicated everything they wanted to (86% vs 95%) 19. A quarter of clinicians showed some recognition of this, reporting a belief that patient experience of a remote video consultation was worse than that in a face-to-face clinic 18 19. This echoes findings from primary care, where general dissatisfaction with video consultations among both patients and practitioners has been reported, emphasising a belief that the best therapeutic care is delivered in person 7.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed a survey study of patient and staff perceptions of video consultations conducted from an older adult outpatient unit in the UK found high levels of satisfaction with this format, particularly among patients 6. In contrast, however, an interview study with patients and clinicians at an orthopaedic centre in the UK found some clinicians perceived video call assessments to be less accurate and more likely to result in worsening of a patients’ condition; this corresponded to some patients’ experiencing slower rehabilitation and perceiving remote appointments to be less effective than face to face 18. This may help to explain, in part, the results of a mixed methods study conducted in a UK outpatient department following the rapid implementation of a remote video consultation platform which indicated that, while all patients reported that the consultations met their needs, they were less satisfied than clinicians that they had communicated everything they wanted to (86% vs 95%) 19.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly to previous literature, participants in this study reported that the diagnostic accuracy of virtual clinics may be less accurate than face-to-face appointments due to the inability to complete a hands-on assessment; this may lead to patients being rebooked for further appointments after their virtual consultation (Glass and Bickler, 2021). In future, there may be scope for further development of the virtual clinics to incorporate hybrid models where the patient can be efficiently reviewed virtually and/or face-to-face according to their needs, as recommended in prior empirical studies and research (Vranceanu et al ., 2019; Gilbert et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the assessment of the patient experience postoperatively in one American study allowed clinicians to identify factors that could be optimised to improve patient care [ 10 ]. The accelerated use of Penthrox at our hospital was brought about by the COVID-19 pandemic, as were remote consultations, which have been assessed in a British tertiary orthopaedic rehabilitation centre [ 11 ]. This study identified means of aligning patient and clinician preferences with the use of remote consultations and relied upon evidence gathered from the patient experience [ 11 ].…”
Section: Introductionmentioning
confidence: 99%